Sintered silicon nitride, wear-resistant member, substrate for semiconductor device, and method for producing sintered silicon nitride
By reasonably adding zirconium to the silicon nitride sintered body and controlling its XRD analysis peak ratio, combined with the use of low-temperature sintered powder, the problem of insufficient strength of silicon nitride sintered body at low temperature is solved, and high strength and excellent insulation are achieved Production of a sintered silicon nitride sintered body.
Patent Information
- Application Number
- CN202380043996.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-27
- Filing Date
- 2023-08-31
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to produce high-strength silicon nitride sintered bodies at low temperatures. Low-temperature sintered bodies usually result in insufficient strength of the silicon nitride sintered bodies, and it is difficult to be used in wear-resistant components and substrates for semiconductor devices.
XRD analysis was performed to control the ratio of α-type and β-type silicon nitride grains and the presence form of zirconium oxide by adding 0.1 mass% or more and 10 mass% to the sintered silicon nitride body to ensure I35.3 /I27.0 is in the range of 0.01~0.5, I33.9/I27.0 is in the range of 0~1.0, and is sintered at a temperature below 1650℃. The pressure change of the firing chamber is controlled by filling powder to suppress the pressure of the firing chamber. Excessive reduction of zirconium.
It has achieved the production of silicon nitride sintered bodies with a strength of up to 600MPa or above at low temperatures, and has excellent wear resistance and insulation properties, and is suitable for wear-resistant components and substrates for semiconductor devices.
Smart Images

Figure CN119301092A_ABST
Abstract
Description
Technical Field
[0001] The embodiments described below generally relate to a silicon nitride sintered body, a wear-resistant member, a semiconductor device substrate, and a method for producing a silicon nitride sintered body. Background Art
[0002] Silicon nitride sintered bodies are used in various fields because they make full use of high strength. For example, in International Publication No. 2020 / 121752 (Patent Document 1), silicon nitride sintered bodies are used for wear-resistant parts such as bearing balls. In International Publication No. 2020 / 044974 (Patent Document 2), silicon nitride sintered bodies are used for semiconductor device substrates. According to Patent Document 1, a silicon nitride sintered body with a three-point bending strength of more than 900MPa is obtained. According to Patent Document 2, a silicon nitride sintered body with a three-point bending strength of more than 700MPa is obtained.
[0003] In the manufacturing methods described in Patent Documents 1 and 2, a silicon nitride sintered body is produced by high-temperature sintering in the range of 1600 to 2000°C. Generally, the sintering furnace for sintering the silicon nitride sintered body is an electric furnace. In recent years, the demand for decarburization has increased. In the manufacture of silicon nitride sintered bodies, in order to reduce the emission of carbon dioxide, it is believed that lowering the sintering temperature is effective.
[0004] For example, Japanese Patent Gazette No. 5811391 (Patent Document 3) discloses a method of using a filling powder in a firing chamber. In Patent Document 3, the use of the filling powder suppresses the influence of SiO gas and Mg gas discharged from the degreased body. However, the firing temperature is 1550 to 1900°C. The firing temperature in the manufacturing method described in Patent Document 3 is equivalent to the firing temperature described in Patent Documents 1 and 2.
[0005] For example, Japanese Patent No. 5062402 (Patent Document 4) discloses that the sintering is performed at 1300-1375° C. by reaction sintering. According to the manufacturing method described in Patent Document 4, although the sintering is performed at a low temperature, the strength of the obtained silicon nitride sintered body is about 140 MPa. With such low strength, it is difficult to use the silicon nitride sintered body as a wear-resistant component or a substrate for a semiconductor device.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2020 / 121752
[0009] Patent Document 2: International Publication No. 2020 / 044974
[0010] Patent Document 3: Japanese Patent No. 5811391
[0011] Patent Document 4: Japanese Patent No. 5062402 Summary of the invention
[0012] Problems to be solved by the invention
[0013] As described above, conventionally, there is no silicon nitride sintered body that can be fired at a low temperature and has high strength. Embodiments of the present invention are to address such a problem, and an object of the present invention is to provide a silicon nitride sintered body that can be fired at a low temperature and has high strength.
[0014] Means used to solve problems
[0015] The silicon nitride sintered body according to the embodiment contains 0.1 mass % or more and 10 mass % or less of zirconium in terms of oxide. When an XRD analysis (2θ) is performed on any cross section of the silicon nitride sintered body, the strongest peak intensity detected at 35.3°±0.2° based on the α-type silicon nitride grains is set as I 35.3 The strongest peak detected based on β-type silicon nitride grains at 27.0°±0.2° is set as I 27.0 , the strongest peak detected based on zirconium nitride at 33.9°±0.2° is set as I 33.9 In the case of 0.01≤I 35.3 / I 27.0 ≤0.5 and 0≤I 33.9 / I 27.0 ≤1.0. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 FIG. 1 is a schematic diagram showing a bearing ball as an example of a wear-resistant member.
[0017] Figure 2 This is a schematic diagram showing an example of a substrate for a semiconductor device.
[0018] Figure 3 It is a top view showing an example of a firing chamber.
[0019] Figure 4 It is a side view showing another example of the firing chamber.
[0020] Figure 5 This is a graph showing an example of the XRD analysis result of the silicon nitride sintered body according to the embodiment. DETAILED DESCRIPTION
[0021] The silicon nitride sintered body according to the embodiment contains 0.1 mass % or more and 10 mass % or less of zirconium in terms of oxide. When an XRD analysis (2θ) is performed on any cross section of the silicon nitride sintered body, the strongest peak intensity detected at 35.3°±0.2° based on the α-type silicon nitride grains is set as I 35.3 The strongest peak detected based on β-type silicon nitride grains at 27.0°±0.2° is set as I 27.0 , the strongest peak detected based on zirconium nitride at 33.9°±0.2° is set as I 33.9 In the case of 0.01≤I 35.3 / I 27.0 ≤0.5 and 0≤I 33.9 / I 27.0 ≤1.0.
[0022] The silicon nitride sintered body involved in the embodiment contains zirconium of 0.1 mass % or more and 10 mass % or less in terms of oxide conversion. Zirconium is converted into an oxide in the form of ZrO2. At least a portion of the zirconium (Zr) component forms a liquid phase around 1300°C. Therefore, zirconium has the effect of lowering the firing temperature. Therefore, in order to perform firing at low temperatures, it is effective to contain zirconium of 0.1 mass % or more and 10 mass % or less in terms of oxide conversion. If the zirconium content is less than 0.1 mass % in terms of oxide conversion, the addition effect is small. If the zirconium content exceeds 10 mass % in terms of oxide conversion, more zirconium nitride is formed. In addition, there is the possibility that the voids become larger. Therefore, the strength and insulation properties are reduced. Therefore, the zirconium content is preferably in the range of 0.1 mass % or more and 10 mass % or less in terms of oxide conversion, and more preferably in the range of 0.5 mass % or more and 6 mass % or less.
[0023] In addition, an XRD analysis (2θ) was performed on an arbitrary cross section of the silicon nitride sintered body according to the embodiment. In the analysis results, the strongest peak intensity detected at 35.3°±0.2° based on the α-type silicon nitride grains was set as I 35.3 The strongest peak intensity detected based on β-type silicon nitride grains at 27.0°±0.2° is set as I 27.0 , the strongest peak intensity detected based on zirconium nitride at 33.9°±0.2° is set as I 33.9 In the case of 0.01≤I 35.3 / I 27.0 ≤0.5 and 0≤I 33.9 / I 27.0 ≤1.0.
[0024] First, the method of XRD analysis (2θ) is described. In XRD analysis, any cross section of the silicon nitride sintered body is used as the measurement surface. A cross section with a surface roughness Ra of less than 1 μm is used as the measurement surface. In XRD analysis, a Cu target (Cu-Kα) is used. The tube voltage is set to 40 kV, the tube current is set to 40 mA, the scanning speed is set to 2.0° / min, the slit (RS) is set to 0.15 mm, and the scanning range (2θ) is set to 10°~50° to perform XRD analysis. Through XRD analysis, qualitative analysis or quantitative analysis corresponding to the crystalline compound can be performed. The D8 ADVANCE manufactured by BRUKER or a device with equivalent performance is used in the measurement.
[0025] In the obtained analysis results, the strongest peak intensity detected based on the α-type silicon nitride grains at 35.3°±0.2° is set as I 35.3 The strongest peak detected based on β-type silicon nitride grains at 27.0°±0.2° is set as I 27.0 , the strongest peak detected based on zirconium nitride at 33.9°±0.2° is set as I 33.9 .
[0026] The so-called strongest peak refers to the peak with the largest intensity among the peaks detected respectively within the specified range. As the "intensity", the intensity of the peak top is used. In addition, as long as the peak top is within the specified range, the lower end of the peak may also exceed the specified range. The peak based on α-type silicon nitride grains also includes α-type SiAlON (also known as silicon aluminum oxynitride ceramics or sialon ceramics). The peak based on β-type silicon nitride grains also includes β-type SiAlON. The presence of α-type silicon nitride grains and β-type silicon nitride grains in the silicon nitride sintered body can be confirmed by other XRD peaks. For example, if α-type silicon nitride grains exist, peaks can be detected at 35.3°±0.2° and 31.0°±0.2°. In addition, if β-type silicon nitride grains exist, peaks can be detected at 27.0°±0.2° and 33.7°±0.2°. In other words, when peaks are detected at 35.3°±0.2° and 31.0°±0.2°, it is determined that α-type silicon nitride grains exist in the silicon nitride sintered body. Similarly, if peaks are detected at 27.0°±0.2° and 33.7°±0.2°, it is determined that β-type silicon nitride grains exist in the silicon nitride sintered body.
[0027] Regarding zirconium nitride, its presence can be confirmed by qualitative analysis if necessary. If zirconium nitride is not detected by qualitative analysis or quantitative analysis, it is considered that 33.9 The peak does not exist, that is, I 33.9= 0. As long as the silicon nitride sintered body containing zirconium can be confirmed by simple qualitative analysis or quantitative analysis, the peak detected at 33.9°±0.2° can be identified as a peak based on zirconium nitride (I 33.9 ).
[0028] Satisfy 0.01≤I 35.3 / I 27.0 ≤0.5, which means that both α-type silicon nitride grains and β-type silicon nitride grains exist. α-type silicon nitride grains are round particles with an aspect ratio that is easily less than 2. β-type silicon nitride grains tend to be slender particles with an aspect ratio of more than 2. The α-type silicon nitride grains enter the gaps between the slender β-type silicon nitride grains, thereby densifying the silicon nitride sintered body and improving the strength of the silicon nitride sintered body. As a result, as described later, even with a low-temperature sintering temperature of less than 1650°C, a high-strength silicon nitride sintered body can be obtained.
[0029] The main component of the silicon nitride sintered body is silicon nitride. 35.3 / I 27.0 is less than 0.5, which means that the β-type silicon nitride grains are contained in the silicon nitride sintered body in the largest amount by mass. That is to say, the mass ratio of β-type silicon nitride grains is greater than the mass ratio of α-type silicon nitride grains. In addition, the peaks appearing in the XRD analysis are affected by composition, crystallinity, amount present, orientation, etc. Among the peaks related to β-type silicon nitride grains, the peak detected at 27.0°±0.2° is likely to be the largest. In addition, among the peaks related to α-type silicon nitride grains, the peak detected at 35.3°±0.2° is likely to be the largest. By controlling the maximum peak intensity I based on the α-type silicon nitride grains 35.3 and the maximum peak intensity based on other components relative to the maximum peak intensity I based on the β-type silicon nitride grains that are the main component 27.0 The ratio can seek optimization of the organization.
[0030] If I 35.3 / I 27.0 In the range of 0.01 to 0.5, the α-type silicon nitride grains are distributed in the gaps between the β-type silicon nitride grains. The elongated β-type silicon nitride grains are intricately entangled, and the α-type silicon nitride grains fill the gaps, which is related to the improvement of strength. 35.3 / I 27.0 If the ratio is less than 0.01, the amount of α-type silicon nitride grains may be insufficient. The gaps between β-type silicon nitride grains become larger, which may cause the strength of the silicon nitride sintered body to decrease. In addition, voids are easily formed, which may reduce the insulation of the silicon nitride sintered body. 35.3 / I 27.0If the ratio is larger than 0.5, the β-type silicon nitride grains are insufficient and the slender β-type silicon nitride grains cannot be formed into a complexly entangled shape. As a result, the strength of the silicon nitride sintered body may decrease. Therefore, I 35.3 / I 27.0 It is preferably in the range of 0.01 to 0.5, and more preferably in the range of 0.05 to 0.4.
[0031] I 33.9 is a peak based on zirconium nitride (ZrN). When XRD analysis is performed on the silicon nitride sintered body involved in the embodiment, 0≤I 33.9 / I 27.0 ≤1.0.I 33.9 / I 27.0 is less than 1.0, which means that the amount of zirconium nitride present relative to the β-type silicon nitride grains is suppressed. 33.9 / I 27.0 When the ratio exceeds 1.0, the amount of zirconium nitride increases, and the strength of the silicon nitride sintered body decreases. In addition, since zirconium nitride is a conductive material, the insulation of the silicon nitride sintered body decreases. 33.9 / I 27.0 It is preferably in the range of 0 to 1.0, and more preferably in the range of 0 to 0.6. 33.9 / I 27.0 = 0, indicating that ZrN does not exist or I is not detected 33.9 (Below the detection limit).
[0032] In the XRD analysis, the strongest peak intensity detected at 28.2°±0.2° based on zirconium oxide was set as I 28.2 In the case of 28.2 / I 27.0 ≤0.30. In addition, the strongest peak intensity detected based on zirconium oxide at 30.1°±0.2° is set as I 30.1 In the case of 30.1 / I 27.0 ≤0.30.
[0033] The presence of a peak based on zirconium oxide indicates that at least a portion of the zirconium in the silicon nitride sintered body exists as zirconium oxide. Examples of zirconium oxide include ZrO2 and composite Zr oxides. For example, when aluminum oxide is used as a sintering aid, a Zr-Al-O compound is sometimes formed as a composite Zr oxide. Similarly, when magnesium oxide is used as a sintering aid, a Zr-Mg-O compound is sometimes formed as a composite Zr oxide. Composite Zr oxides may also contain partially stabilized zirconium oxide, stabilized zirconium oxide, and the like. Examples of partially stabilized zirconium oxide or stabilized zirconium oxide include oxides in which yttrium oxide, cerium oxide, magnesium oxide, and the like are solid-dissolved in zirconium oxide.
[0034] Zirconium oxide has a monoclinic, tetragonal or cubic crystal structure. 28.2 or I 30.1 , which means that the zirconium oxide is monoclinic or tetragonal. Monoclinic is a crystal structure that is stable at room temperature. Tetragonal is a crystal structure that is stable near 1170°C. Cubic is a crystal structure that is stable near 2370°C. In the XRD analysis, a peak of zirconium oxide is detected, which indicates the presence of crystalline zirconium oxide. In the silicon nitride sintered body, zirconium oxide exists in the grain boundary phase. The grain boundary phase can be strengthened by the presence of a crystalline compound of zirconium oxide in the grain boundary phase. As a result, the strength of the silicon nitride sintered body can be further improved.
[0035] Satisfy 0.01≤I 28.2 / I 27.0 ≤0.30 or 0.02≤I 30.1 / I 27.0 ≤0.30, which means that the zirconium oxide is monoclinic or tetragonal. In addition, 0.01≤I 28.2 / I 27.0 ≤0.30 and 0.02≤I 30.1 / I 27.0 ≤0.30, or only one of them may be satisfied. In addition, when only one of them is satisfied, it is preferred that no I 28.2 or I 30.1 In addition, if any peak of I 28.2 If I 30.1 This means that zirconium oxide is tetragonal.
[0036] The main body is composed of monoclinic or tetragonal crystals that are stable from room temperature to around 1000°C. On the other hand, cubic crystals are stable around 2370°C. Monoclinic or tetragonal crystals are the main body, which means that the structure sintered at a low temperature below 1650°C is stable. If there are many cubic crystals, it means that the heat transmitted to the sintered body through the sintering process is unstable. This may be the reason why the size and voids of the zirconium oxide cannot be controlled. In other words, it is preferred that there is less or no cubic zirconium oxide. Cubic zirconium oxide can be observed using TEM (transmission electron microscope) or the like.
[0037] In addition, it is preferred that tetragonal zirconium oxide is present. As described later, if zirconium oxide reacts with sintering aids such as magnesium oxide during the sintering process, zirconium oxide becomes tetragonal and stable. In other words, the presence of tetragonal zirconium oxide indicates that zirconium oxide is stable by reacting with other sintering aids. As other sintering aids, components that form partially stabilized zirconium oxide can be cited.
[0038] Therefore, I 28.2 / I 27.0 It is preferably in the range of 0.01 to 0.30, and more preferably in the range of 0.05 to 0.20. 30.1 / I 27.0 It is preferably in the range of 0.02 to 0.30, and more preferably in the range of 0.05 to 0.20.
[0039] In addition, in the XRD analysis, the strongest peak intensity detected at 36.7°±0.2° was set as I 36.7 , the strongest peak intensity detected at 41.9°±0.2° is set as I 41.9 In the case of 36.7 / I 27.0 ≤0.50 or 0≤I 41.9 / I 27.0 ≤0.50. It can also satisfy 0≤I 36.7 / I 27.0 ≤0.50 and 0≤I 41.9 / I 27.0 ≤0.50 for both parties, or only one party can be satisfied.
[0040] The peak detected at 36.7°±0.2° and the peak detected at 41.9°±0.2° are based on crystalline compounds of the grain boundary phase. The peaks observed in these two ranges are based on crystalline compounds other than zirconium oxide, indicating that crystalline compounds other than zirconium oxide exist in the grain boundary phase. As these crystalline compounds, compounds containing one or more selected from rare earth elements, aluminum, and magnesium can be listed. As rare earth elements, yttrium and lanthanide elements can be listed. As crystalline compounds, oxides, nitrides or oxynitrides containing elements selected from rare earth elements, aluminum, and magnesium can be listed. Each can also be a composite oxide, a composite nitride, or a composite oxynitride.
[0041] As described later, rare earth element oxides, magnesium oxides, and aluminum oxides can be cited as sintering aids. Rare earth elements and magnesium are dissolved in zirconium oxide to form composite Zr oxides. Composite Zr oxides become stable phases. Aluminum and oxygen are also sometimes dissolved in silicon nitride to form SiAlON.
[0042] Satisfy 0≤I 36.7 / I 27.0 ≤0.50 or 0≤I 41.9 / I 27.0 ≤0.50, which means that it helps the sintering aid to form a stable phase. In other words, the amount of crystalline compounds in the grain boundary phase is suppressed. As a result, the strengthening of the grain boundary phase brought about by the pinning effect of the zirconium oxide particles can be sought. In other words, it is preferred that 36.7 / I 27.0 or I 41.9 / I 27.0 If they are both greater than 0.50, there will be a large number of crystalline compounds other than zirconium oxide with low pinning effect. 36.7 / I 27.0 It is preferably in the range of 0 or more and 0.50 or less, and more preferably in the range of 0 or more and 0.4 or less. 0≤I 41.9 / I 27.0 ≤0.50 is preferably in the range of 0 to 0.5, and more preferably in the range of 0 to 0.4.
[0043] In addition, the presence of a crystalline compound in the grain boundary phase can improve the strength and hardness of the silicon nitride sintered body. This is because the crystalline compound phase is harder than the amorphous phase. The improvement of strength and hardness is related to the improvement of wear resistance. Therefore, it is preferred to satisfy 0 36.7 / I 27.0 ≤0.50, 0 41.9 / I 27.0 ≤0.50, 0 36.7 / I 27.0 ≤0.50 and 0 41.9 / I27.0 ≤ 1 or more of 0.50.
[0044] Figure 5 This is a graph showing an example of the XRD analysis result of the silicon nitride sintered body according to the embodiment. Figure 5 In the figure, the peaks marked with triangle symbols are peaks based on α-type silicon nitride grains. The peaks marked with circle symbols are peaks based on β-type silicon nitride grains. The peaks marked with square symbols are peaks based on monoclinic zirconium oxide. The peaks marked with diamond symbols are peaks based on tetragonal zirconium oxide.
[0045] exist Figure 5 In the analysis results shown, I 35.3 / I 27.0 In the range of 0.01 to 0.5, I 33.9 / I 27.0 In the range of 0 or more and 1.0 or less. 30.1 / I 27.0 In the range of 0.02 or more and 0.30 or less, I 28.2 / I 27.0 In the range of 0.01 or more and 0.30 or less. Figure 5 In the analysis results shown, no peaks were detected in the range of 36.7°±0.2° and 41.9°±0.2°. 36.7 / I 27.0 and I 41.9 / I 27.0 is zero.
[0046] In addition, the silicon nitride sintered body preferably contains zirconium oxide particles. For example, the zirconium oxide particles are dispersed in the grain boundary phase in the silicon nitride sintered body. In a measurement area of 100 μm×100 μm in any cross section, the average particle size of the zirconium oxide particles is preferably 0.05 μm or more and 2 μm or less.
[0047] As mentioned above, it is preferred that zirconium oxide is a crystalline compound having a prescribed XRD peak. The particle size of the so-called zirconium oxide particles is the size of the particles of zirconium oxide. The zirconium oxide particles may be either single crystal or polycrystalline. The average particle size of the zirconium oxide particles is preferably in the range of 0.05 μm or more and 2 μm or less. If the average particle size is in the range of 0.05 μm or more and 2 μm or less, the function of strengthening the grain boundary phase is improved. If the average particle size is less than 0.05 μm, there is a possibility that the function of strengthening the grain boundary phase is insufficient. In addition, if the average particle size exceeds 2 μm, there is a possibility that the gap between the silicon nitride grains and the zirconium oxide particles becomes larger. If the gap becomes larger, it becomes the cause of the occurrence of voids. Therefore, the average particle size of the zirconium oxide particles is preferably in the range of 0.05 μm or more and 2 μm or less, and more preferably in the range of 0.1 μm or more and 1 μm or less.
[0048] In addition, in the measurement area of 100 μm×100 μm, the total area of the zirconium oxide particles is preferably in the range of 0.01% to 15%. By making the area ratio relative to the measurement area of 100 μm×100 μm 0.01% to 15%, the zirconium oxide particles can be distributed more evenly. By controlling the average particle size and area ratio of the zirconium oxide particles, the effect can be further improved. It is more preferred that the total area of the zirconium oxide particles is in the range of 0.01% to 15% regardless of which measurement area of any cross section is measured.
[0049] The method for measuring the average particle size and area ratio of zirconium oxide particles is described. First, an arbitrary cross section is obtained from a silicon nitride sintered body. As long as the cross section can be observed with a scanning electron microscope (SEM), its pretreatment is not limited. For example, it is preferred to observe the cross section of ion milling with SEM. In the observation based on SEM, a cross section subjected to XRD analysis can also be used. In this case, first, a magnified photograph (SEM photograph) of 1000 times or more is taken by SEM photography. A measurement area of 100μm×100μm is randomly extracted from the magnified photograph. The particle size of each zirconium oxide particle reflected in the measurement area is measured. The distance between the two most separated points on the outer edge of the particle is measured as the particle size. The average value of the particle size measured in the measurement area of 100μm×100μm is taken as the average particle size. Furthermore, when it is difficult to identify zirconium oxide particles in the SEM photograph, element mapping of zirconium and oxygen can also be performed by energy dispersive X-ray spectroscopy (EDX). When a composite Zr oxide is contained, zirconium oxide particles can be identified by using the distribution of the composite elements in combination. For example, by using the element distribution of EDX, a region where zirconium and oxygen overlap can be identified as a zirconium oxide particle.
[0050] The maximum diameter of the voids in the silicon nitride sintered body is preferably 3 μm or less. In the determination of the maximum diameter of the voids, an SEM photograph of any cross section of the silicon nitride sintered body is used. The SEM photograph used in the determination of the particle size of the zirconium oxide particles can also be used in the determination of the maximum diameter of the voids. Measure the long diameter of the voids reflected on the SEM photograph. Measure the distance between the two farthest points on the outer edge of the void as the long diameter of the void. In the voids reflected in the measurement area of 100 μm×100 μm, the largest long diameter is taken as the maximum diameter of the void. It is more preferred that the maximum diameter of the void is 1 μm or less.
[0051] The void can be observed by analyzing the SEM photo using image analysis software. As the image analysis software, Image J or software equivalent thereto is used. In the SEM photo of the cross section, a contrast is generated between the void and other parts. For example, the color of the void looks darker and thicker than the color of the part other than the void. By using the difference in this contrast to binary the SEM photo, the void and other parts can be distinguished.
[0052] As a threshold value for binarization, a value that can be obtained by the "modal method" or the "recognition analysis binarization method" is used. When the image analysis software has the function of the recognition analysis binarization method, the recognition analysis binarization method of the image analysis software is used. In the recognition analysis binarization method, the threshold value is fundamentally determined by the analysis software. Therefore, it is easy to identify the void. For example, in the SEM photo, the area that can be seen as white around the void is the boundary between the void and the silicon nitride sintered body. Therefore, the area that can be seen as white around the void should not be counted as a void. In addition, in the SEM photo, the silicon nitride sintered body is gray. By using the threshold value obtained by the "modal method" or the "recognition analysis binarization method", the void can be represented by black, and the white area around the void and the silicon nitride sintered body can be represented by white. By using a binarized image, the void and other areas reflected on the SEM photo can be identified.
[0053] For example, in a measurement area of 100 μm×100 μm, the average particle size of the zirconium oxide particles is preferably 0.05 μm to 2 μm, the total area of the zirconium oxide particles is 0.01% to 15%, and the maximum diameter of the voids is 3 μm or less. More preferably, in a measurement area of 100 μm×100 μm, the average particle size of the zirconium oxide particles is 0.1 μm to 1 μm, the total area of the zirconium oxide particles is 0.01% to 15%, and the maximum diameter of the voids is 1 μm or less.
[0054] As long as it is a silicon nitride sintered body having the above-mentioned structure, even if the firing temperature is lower than 1650°C, a three-point bending strength of more than 600MPa can be obtained. In addition, a dielectric strength of more than 13kV / mm can be obtained. The three-point bending strength can be measured according to JIS-R-1601 (2008). The dielectric strength can be measured according to the dielectric breakdown strength of JIS-C-2141 (1992). Furthermore, JIS-R-1601 corresponds to ISO14704. JIS-C-2141 corresponds to IEC672-2.
[0055] Such a silicon nitride sintered body can be used in various fields. The silicon nitride sintered body according to the embodiment can be used for wear-resistant parts. Figure 1 FIG. 1 is a schematic diagram showing a bearing ball as an example of a wear-resistant member. Figure 1 1 represents a bearing ball. The bearing ball 1 is a true spherical ball. The bearing ball 1 formed of a silicon nitride sintered body has excellent wear resistance.
[0056] The bearing has a structure in which a bearing ball 1 is arranged between an inner wheel and an outer wheel. Generally, the inner wheel and the outer wheel are formed of bearing steel. If the bearing is rotated at a high speed, electrolytic corrosion sometimes occurs. When the bearing ball 1 involved in the embodiment is used, the electrical corrosion can be suppressed because the silicon nitride sintered body has high insulation.
[0057] In addition, friction is generated on the surface of the bearing ball 1. The silicon nitride sintered body according to the embodiment has excellent durability due to its excellent wear resistance. As wear-resistant parts, in addition to bearing balls, there are various roller materials such as those used for rolling, engine components such as cam rollers, bearing components, compressor impellers, gas turbine blades, friction stir welding tool components, etc.
[0058] Furthermore, the silicon nitride sintered body according to the embodiment can be used as a substrate for a semiconductor device. Figure 2 This is a schematic diagram showing an example of a substrate for a semiconductor device. Figure 2 In the figure, 2 is a substrate for a semiconductor device. Figure 2 In the figure, a quadrilateral substrate is exemplified, but the shape of the substrate may be circular, L-shaped, or U-shaped.
[0059] In the semiconductor device substrate 2, a circuit part and a semiconductor element, etc. can be provided. The circuit part is a metal plate or a metallized layer, etc. The circuit part is bonded to the substrate through a bonding layer as needed. In addition, a semiconductor device is obtained by mounting a semiconductor element, etc. on the circuit part. By using the silicon nitride sintered body involved in the embodiment, a semiconductor device substrate 2 having excellent strength and insulation can be provided.
[0060] Next, a method for producing a silicon nitride sintered body according to an embodiment will be described. The method for producing the silicon nitride sintered body according to an embodiment is not particularly limited as long as it has the above-mentioned structure. Here, a method for obtaining a silicon nitride sintered body with a high yield will be described.
[0061] The method for manufacturing a silicon nitride sintered body according to the embodiment comprises a forming body production step, a degreased body production step, a degreased body configuration step, a filling powder configuration step, and a firing step. The forming body can be produced by mixing silicon nitride powder and at least zirconium compound powder and forming the mixed powder. The degreased body can be produced by degreasing the forming body. The degreased body and the filling powder are configured in a firing chamber. In the firing step, the degreased body is fired at a temperature lower than 1650° C. in the firing chamber configured with the filling powder.
[0062] Figure 3 It is a top view showing an example of a firing chamber. Figure 4 It is a side view showing another example of the firing chamber. Figure 3 and Figure 4 In the figure, reference numeral 3 denotes a firing chamber, reference numeral 4 denotes an outer wall, reference numeral 5 denotes an inner wall, reference numeral 6 denotes a filling powder, reference numeral 7 denotes a degreased body, reference numeral 8 denotes a lid portion, and reference numeral 9 denotes a table portion. Figure 3 and Figure 4 This is a diagram schematically showing the interior of a firing chamber of a firing furnace.
[0063] First, a process of making a molded body is performed. At least zirconium compound powder is mixed into silicon nitride powder. The silicon nitride contained in the silicon nitride powder is preferably α-type. The α-ratio of silicon nitride is preferably 90% or more. The amount of oxygen contained in silicon nitride is preferably 2% by mass or less, and the average particle size of silicon nitride is preferably 3 μm or less. The α-type silicon nitride powder grows into β-type grains during the sintering process. By accompanying grain growth, both α-type silicon nitride grains and β-type silicon nitride grains can exist. Furthermore, β-type silicon nitride powder can also be added as needed.
[0064] As zirconium compound powder, zirconium oxide powder or composite Zr oxide can be cited. The ratio of zirconium oxide in the zirconium compound powder is preferably in the range of 90 mass % or more and 100 mass % or less. Any one or more of monoclinic zirconium oxide powder, tetragonal zirconium oxide powder, and cubic zirconium oxide powder can be used. Monoclinic zirconium oxide powder is preferably used as the raw material powder. Monoclinic crystal is stable at room temperature. In addition, as a composite Zr oxide, partially stabilized zirconium oxide or stabilized zirconium oxide can be cited. Preferably, partially stabilized zirconium oxide or stabilized zirconium oxide is tetragonal. Partially stabilized zirconium oxide or stabilized zirconium oxide of tetragonal crystal is stable at room temperature. Therefore, the deviation of crystal change caused by the influence of heat in the firing process can be reduced. The average particle size of the zirconium compound powder is preferably 3 μm or less. Zirconium oxide becomes a sintering aid for low-temperature firing below 1650°C. In addition, the amount of zirconium compound powder added is preferably in the range of 0.1 mass % or more and 10 mass % or less in terms of zirconium oxide. Within this range, the above-mentioned XRD peak can be easily controlled.
[0065] A sintering aid other than zirconium oxide may be added to the raw material powder. For example, one or more elements selected from rare earth elements, aluminum and magnesium are selected, and one or more oxides, nitrides and oxynitrides selected from the elements are used as sintering aids. The oxides, nitrides and oxynitrides may be composite oxides, composite nitrides and composite oxynitrides, respectively. Rare earth elements include yttrium and lanthanide elements.
[0066] In particular, it is preferred that oxides are added as sintering aids. Alumina or magnesium oxide reacts with zirconium oxide in the sintering process to form a composite Zr oxide. Stabilized zirconium oxide or partially stabilized zirconium oxide can be formed according to the amount of magnesium dissolved in the solid solution. Stabilized zirconium oxide or partially stabilized zirconium oxide is easy to become a tetragonal crystal.
[0067] In addition, when zirconium oxide reacts with aluminum oxide, a Zr-Al-O system crystalline compound is formed. In addition, aluminum oxide sometimes reacts with silicon nitride to form α-type SiAlON or β-type SiAlON. Zirconium oxide added in a monoclinic state reacts with other sintering aids and changes to tetragonal crystals to become stable. The part of monoclinic zirconium oxide that has not reacted with other sintering aids can also remain in its original state.
[0068] Rare earth elements have the function of forming a stabilizing phase by solid solution in zirconium oxide. In addition, rare earth elements are sintering aids that are effective in improving sinterability. Rare earth elements can form crystalline compounds by reacting with silicon nitride, aluminum and magnesium. For example, there can be listed crystalline compounds such as rare earth elements-Al-O system, rare earth elements-Mg-O system, rare earth elements-Al-Mg-O system, rare earth elements-Al-ON system, rare earth elements-Mg-ON system, rare earth elements Al-Mg-ON system, rare earth elements-Si-Al-O system, rare earth elements-Si-Mg-O system, rare earth elements-Si-Al-Mg-O system, rare earth elements-Si-Al-ON system, rare earth elements-Si-Mg-ON system, and rare earth elements-Si-Al-Mg-ON system. These crystalline compounds are very important for controlling I 36.7 or I 41.9 is effective.
[0069] The addition amount of the compound of the element selected from rare earth elements, aluminum and magnesium is preferably in the range of 1 mass % or more and 15 mass % or less in total. The compound is one or more selected from oxides, nitrides and oxynitrides. In addition, as an oxide of aluminum or an oxide of magnesium, spinel (MgAl2O4) can also be used in addition to Al2O3 and MgO.
[0070] In addition, as a sintering aid other than the above, silicon oxide can be cited. Silicon oxide has the effect of lowering the eutectic temperature with zirconium oxide. Therefore, it has the effect of lowering the sintering temperature. Preferably, the amount of silicon oxide added is in the range of 0.1 mass % or more and 5 mass % or less. Impurity oxygen contained in the silicon nitride powder can also be added in the form of silicon oxide.
[0071] Silicon nitride powder and zirconium oxide powder (including composite Zr oxide) and other sintering aid powders are mixed. In addition, a binder and a solvent are mixed to prepare a raw material powder slurry. Next, the raw material powder slurry is used to make a molded body. In the production of the molded body, various methods such as molding, cold isostatic pressing (CIP), and scraper coating can be used.
[0072] Next, a step of making a degreased body by degreasing the molded body is performed. The degreasing step is a step of removing or reducing the binder and solvent in the molded body. The degreasing step is preferably performed in a temperature range of 400° C. to 600° C. The degreasing step can be performed in nitrogen, in the atmosphere, or in a vacuum. A degreased body is obtained by performing the degreasing step.
[0073] Next, the step of placing the produced degreased body in a sintering chamber is performed. Figure 4In the example shown, the degreased body 7 is arranged on the table surface 9 in the firing chamber. A firing container may be used as required. In addition, the degreased bodies 7 may be stacked one on another, and the firing containers may be stacked one on another. When the degreased bodies 7 are stacked one on another, a powder coating or a backing plate may be arranged between the degreased bodies 7.
[0074] Next, a step of arranging the filling powder in the sintering chamber is performed. The sintering chamber 3 is a room in the sintering furnace, and is a room for sintering the degreased body 7. In addition, the sintering chamber 3 has an outer wall 4 and an inner wall 5. The filling powder 6 is arranged in the gap between the outer wall 4 and the inner wall 5. The space where the degreased body 7 is arranged is connected to the space between the outer wall 4 and the inner wall 5. The step of arranging the filling powder 6 can be performed after the degreased body 7 is arranged in the sintering chamber 3, and can also be performed before the degreased body 7 is arranged in the sintering chamber 3.
[0075] like Figure 3 As shown, the filling powder 6 is arranged in the space between the outer wall 4 and the inner wall 5. The space surrounds the degreased body 7 in the horizontal direction. Figure 4 As shown, a cover 8 may be arranged above the degreased body 7. When the cover 8 is arranged, the filling powder 6 is also arranged in the space inside the cover 8. The space where the degreased body 7 is arranged is connected to the space inside the cover 8. When the filling powder 6 cannot be arranged in the cover 8, the filling powder 6 may be arranged on the cover 8.
[0076] exist Figure 3 and Figure 4 In the example shown, a filling powder 6 is arranged between the outer wall 4 and the inner wall 5. When there is no outer wall 4 and inner wall 5 in the firing chamber 3, the filling powder 6 may be arranged around the firing container that accommodates the degreased body 7. Similarly, when there is no cover 8, the filling powder 6 may be arranged on the firing container. Furthermore, in the firing chamber 3, it is not necessary to form a completely closed space by the outer wall 4, the inner wall 5 or the firing container. The gas coming out of the degreased body 7 may also come to the outside from the outer wall 4, the inner wall 5 or the firing container. Therefore, a hole or a passage for gas circulation may be provided in the outer wall 4, the inner wall 5 or the firing container.
[0077] The filler powder 6 is preferably one or more selected from silicon nitride, silicon oxide, magnesium oxide and talc. The silicon nitride powder may be either α-type or β-type. In addition, talc is a composite oxide represented by MgO·SiO2. These filler powders 6 are effective for partial pressure control in the firing process.
[0078] Next, a firing process is performed to fire the degreased body 7 at a temperature lower than 1650°C. The firing temperature is preferably lower than 1550°C. Here, the so-called "low-temperature firing" means firing the degreased body at a temperature lower than 1650°C and further lower than 1550°C. Furthermore, the pressure during firing can be any of normal pressure, pressurization, and reduced pressure. In addition, the firing atmosphere can be any of the air, non-oxidizing atmosphere, and vacuum. In addition, the pressure change in the firing process is preferably less than 0.1MPa. By using the filling powder 6, the pressure change in the firing process can be suppressed to less than 0.1MPa.
[0079] As mentioned above, zirconium oxide powder is an effective sintering aid for sintering at a temperature lower than 1650° C. On the other hand, zirconium oxide easily forms zirconium nitride by reacting with silicon nitride. In particular, zirconium oxide easily forms zirconium nitride by reacting with silicon nitride at around 1600° C.
[0080] In addition, magnesium oxide (MgO) as a sintering aid can form a liquid phase at low temperatures. During the firing process, MgO volatilizes in the form of Mg. The volatilized Mg has a strong reducing property. When the Mg contained in the degreased body 7 volatilizes, it has a strong reducing effect on ZrO2. As a result, ZrO2 is reduced to form Zr. Zr forms ZrN (zirconium nitride) by reacting with nitrogen. Although zirconium oxide or magnesium oxide is an effective sintering aid for low temperature firing, in the past, ZrN that reduces the characteristics was formed more. As a result, I 33.9 / I 27.0 Exceeding 1.0.
[0081] ZrN is mainly formed in the surface portion of the silicon nitride sintered body. The ZrN in the surface portion can be removed by shaving off the surface portion by about tens of μm. On the other hand, the process of shaving off the surface portion involves an increase in manufacturing costs. Therefore, it is preferred to suppress the formation of ZrN in the sintering process. In addition, ZrN has conductivity. If a silicon nitride sintered body containing ZrN is used for bearing balls, it is possible to cause electrolytic corrosion. If a silicon nitride sintered body containing ZrN is used as a substrate for a semiconductor device, it becomes a cause of poor insulation. Furthermore, the vapor pressure of rare earth oxides and alumina is lower than that of ZrO2 and MgO. Therefore, rare earth oxides and alumina are sintering aids with low reducing properties.
[0082] By using the filler powder 6, it is possible to suppress ZrO 2 from being converted into ZrN. In other words, it is possible to suppress ZrO 2 from being reduced. In addition, it is possible to suppress MgO from being reduced.
[0083] If the filler powder 6 is used, the airtightness in the firing chamber 3 is improved. The improvement of the airtightness is related to the suppression of the pressure change in the firing chamber 3. In addition, by using one or more selected from silicon nitride, silicon oxide, magnesium oxide, and talc as the filler powder 6, the pressure change in the firing process can be made less than 0.1 MPa. The vapor pressure of silicon nitride, silicon oxide, magnesium oxide, and talc is equal to or more than the vapor pressure of zirconium oxide. Since the filler powder 6 is reduced earlier than zirconium oxide, the zirconium oxide in the degreased body 7 is difficult to be nitrided.
[0084] For example, when silicon nitride powder or silicon oxide powder is used as the filling powder 6, SiO (silicon monoxide) gas is discharged from the filling powder 6. Since the space in the firing chamber 3 is filled with SiO gas discharged from the filling powder 6, the zirconium oxide in the degreased body 7 becomes difficult to be nitrided. When magnesium oxide or talc is used as the filling powder 6, magnesium is discharged from the filling powder 6 during firing. The pressure of magnesium in the space in the firing chamber 3 increases. As a result, the volatilization of magnesium from the degreased body 7 can be suppressed, and the reduction of ZrO2 due to the volatilization of Mg from the degreased body 7 can be suppressed. As a result, the XRD peaks of zirconium oxide and zirconium nitride can be controlled. In addition, the reduction of MgO added as a sintering aid can be suppressed. Furthermore, experiments conducted by the inventors of the present application confirmed that the Mg present in the space in the firing chamber 3 is difficult to have a reducing effect on the ZrO2 contained in the degreased body 7. That is, it was confirmed that even when the partial pressure of Mg in the space within the firing chamber 3 was high, the reduction reaction of ZrO 2 could be effectively suppressed by suppressing the volatilization of Mg from the degreased body 7 .
[0085] Furthermore, if a large number of degreased bodies 7 are fired at once in order to improve mass productivity, gas is generated at the same time from a large number of degreased bodies 7. As a result, the pressure change in the firing process increases. By exhausting gas from the filling powder 6 and suppressing the amount of gas generated from the degreased body 7, the pressure change in the firing process can be controlled to be less than 0.1 MPa.
[0086] The firing temperature is preferably lower than 1650°C, more preferably lower than 1550°C. As described above, α-type silicon nitride powder is used as the raw material powder. The α-type silicon nitride powder grows into β-type silicon nitride grains through the firing process. By lowering the firing temperature to lower than 1650°C, the grain growth into β-type silicon nitride grains can be suppressed. Thus, the ratio of α-type silicon nitride grains to β-type silicon nitride grains can be controlled. As a result, the I 35.3 / I 27.0 Furthermore, the control of the grain growth of the β-type silicon nitride grains is also related to the distribution control of the zirconium oxide particles. Furthermore, the maximum diameter of the voids in the silicon nitride sintered body can be made 1 μm or less.
[0087] For example, when the same firing furnace (intermittent electric furnace) is used to perform the firing process at 1650°C, the power consumption can be reduced by about 15% compared to when the firing process is performed at 1800°C. In addition, if the firing is performed at a low temperature, the firing can also be performed at normal pressure. Since pressure control is not required, the cost can be reduced. In addition, the life of the setter, insulation material, etc. in the firing furnace can also be extended. Silicon nitride sintered bodies that can be fired at a low temperature are effective in reducing power consumption and reducing costs.
[0088] According to the manufacturing method described above, a silicon nitride sintered body with a relative density of 98% or more can be obtained. The relative density can be obtained by the Archimedean method. Even with low-temperature sintering below 1650°C, the relative density can be made above 98%. In addition, a silicon nitride sintered body with a three-point bending strength of 600MPa or more can be obtained. A silicon nitride sintered body with a dielectric strength of 13kV / mm or more can be obtained. Furthermore, the lower limit of the sintering temperature is not particularly limited, but is preferably above 1200°C. If it is below 1200°C, there is a possibility that the silicon nitride sintered body is not sufficiently densified and the maximum diameter of the voids cannot be below 1μm. Therefore, the sintering temperature is preferably in the range of 1200°C or more and below 1650°C, and more preferably 1300°C or more and below 1550°C.
[0089] As needed, the obtained silicon nitride sintered body may also be subjected to additional heat treatment. As additional heat treatment, hot isostatic pressing (HIP), warpage correction process, etc. may be listed. If HIP treatment is performed, a silicon nitride sintered body with a relative density of more than 99% can be obtained. In addition, by HIP treatment, the three-point bending strength of the silicon nitride sintered body can be increased to more than 900MPa. Furthermore, the heat treatment temperature of the additional heat treatment process is arbitrary. The treatment temperature of the additional heat treatment process is preferably lower than 1650°C, but it can also be performed above 1650°C.
[0090] (Example)
[0091] (Examples 1 to 14, Comparative Examples 1 to 4)
[0092] As raw material powder, α-silicon nitride powder is prepared. The average particle size of α-silicon nitride powder is 3 μm or less, the impurity oxygen content is 1.3 mass%, and the alpha conversion rate is 90% or more. As sintering aid powder, zirconium oxide powder (including composite Zr oxide), yttrium oxide powder, aluminum oxide powder, magnesium oxide powder, spinel powder, and silicon dioxide powder are prepared. The average particle size of the sintering aid powder is 3 μm or less. Silicon nitride powder and sintering aid powder are mixed according to the mixing ratio in Table 1. The mixing ratio is the ratio when the total of silicon nitride powder and sintering aid powder is set to 100 mass%. Furthermore, regarding the crystal structure of zirconium oxide powder (including composite Zr oxide) recorded in Table 1, "monoclinic" means that monoclinic zirconium oxide powder is used. "Tetragonal" means that tetragonal yttrium-stabilized zirconia powder is used.
[0093] The spinel powder of the sintering aid is MgAl2O4.
[0094]
[0095] In the embodiment, at least one of silicon nitride powder, zirconium oxide powder, yttrium oxide powder, aluminum oxide powder, magnesium oxide powder, spinel powder or silicon dioxide powder is mixed in a prescribed amount. In Comparative Example 1, zirconium oxide is not added. In Comparative Example 2, zirconium oxide powder is added in large quantities. In Comparative Example 3, as described later, no filler powder is used for sintering. In Comparative Example 4, as described later, sintering is performed at 1800°C.
[0096] The raw material powders were mixed, and a binder and a solvent were added, and the raw material powder slurry was made by ball milling. Only Example 9 was made by a planetary mill at 400 rpm for 1 hour. After the slurry was dried, it was powdered and molded. The molded body was subjected to a degreasing process at a temperature of 400°C to 600°C.
[0097] Next, the degreased body was placed in a firing chamber. In Examples 1 to 14, Comparative Examples 1 to 2, and Comparative Example 4, filler powder was placed between the outer wall and the inner wall of the firing chamber. In addition, filler powder was placed on the cover of the firing chamber. On the other hand, in Comparative Example 3, filler powder was not placed. The firing process was performed under the conditions shown in Table 2.
[0098] Table 2
[0099]
[0100] Through the above process, a silicon nitride sintered body was produced. In Examples 1 to 14 and Comparative Examples 3 to 4, the zirconium content was in the range of 0.1 mass % or more and 10 mass % or less in terms of oxide conversion. In Comparative Example 1, the silicon nitride sintered body does not contain zirconium. In Comparative Example 2, the zirconium content in the silicon nitride sintered body exceeded 10 mass % in terms of oxide conversion. In Comparative Example 3, since no filler powder was used, the pressure change during the firing process exceeded 0.1 MPa. In Comparative Example 4, since the firing temperature was high, the pressure change during the firing process exceeded 0.1 MPa even if filler powder was used.
[0101] Next, XRD analysis was performed on an arbitrary cross section of each silicon nitride sintered body. The conditions and method of XRD analysis were as described above. Table 3 shows the relationship between the peak intensities observed in the XRD analysis.
[0102] Table 3
[0103]
[0104] As shown in Table 3, regarding the silicon nitride sintered body of the embodiment, I 35.3 / I 27.0 and I 33.9 / I 27.0 In the silicon nitride sintered body of the example, zirconium exists in the form of zirconium oxide. In addition, a peak ratio of 0 means that the peak intensity of the molecule is below the detection limit.
[0105] In contrast, in Comparative Example 2, I 33.9 / I 27.0 More than 1.0. In Comparative Example 2, since the amount of zirconium oxide powder added was large, more ZrN was formed. In Comparative Example 3, since no filler powder was used, more ZrN was formed. In Comparative Example 4, since the sintering temperature was high, silicon nitride and zirconium oxide were formed inside the sintered body, and more zirconium nitride was formed on the surface of the sintered body.
[0106] Next, an arbitrary cross section of the silicon nitride sintered body is photographed by SEM. The average particle size and total area of the zirconium oxide particles are measured using the obtained SEM photographs. In addition, the maximum diameter of the voids is measured. The detailed conditions are as described above. It is confirmed whether the total area of the zirconium oxide particles is within the range of more than 0.01% and less than 15% in any measurement area of 100μm×100μm. In addition, the relative density of the silicon nitride sintered body is measured. The relative density was measured by the Archimedean method. The results are shown in Table 4.
[0107] Table 4
[0108]
[0109] In the silicon nitride sintered body of the example, the average particle size and total area of the zirconium oxide particles were within the specified ranges. In addition, the maximum diameter of the voids was 3 μm or less. The relative density was 96% or more, and the sintered body was sufficiently densified.
[0110] On the other hand, in Comparative Example 1, since zirconium oxide was not added, the voids were large and the relative density was low. In Comparative Example 2, since the amount of zirconium oxide added was large, the voids were large and the relative density was low. In Comparative Example 3, since filler powder was not used, a large amount of zirconium nitride was formed, and the insulation was low as described later. In Comparative Example 4, since the firing temperature was high, a large amount of zirconium nitride was formed. In other words, it was found that the composition of the examples was not suitable for high-temperature firing.
[0111] Next, the three-point bending strength and dielectric strength of each silicon nitride sintered body were measured. The measurement conditions were as described above. Regarding the dielectric strength, whether it was 14 kV / mm or more was measured. The results are shown in Table 5.
[0112] Table 5
[0113]
[0114] As shown in Table 5, the silicon nitride sintered body of the embodiment has excellent three-point bending strength and dielectric strength. Excellent properties can be obtained even at a low temperature of less than 1650° C. In the comparative example, the silicon nitride sintered body is not densified, so the strength and dielectric strength are low.
[0115] Next, the silicon nitride sintered bodies of Examples 1 to 3 were subjected to HIP treatment. The relative density and three-point bending strength after the HIP treatment were measured. The results are shown in Table 6.
[0116] Table 6
[0117]
[0118] As can be seen from Table 6, densification progresses by performing the HIP treatment, and the strength of the silicon nitride sintered body is improved.
[0119] Furthermore, according to the embodiment, the sintering process can be performed at a low temperature lower than 1650° C., so that energy consumption can be reduced.
[0120] The embodiments of the present invention include the following features.
[0121] (Feature 1)
[0122] A silicon nitride sintered body comprising 0.1 mass % or more and 10 mass % or less of zirconium in terms of oxide, wherein:
[0123] When performing XRD analysis (2θ) on an arbitrary cross section, the strongest peak intensity detected at 35.3°±0.2° based on the α-type silicon nitride grains is set as I 35.3 The strongest peak detected based on β-type silicon nitride grains at 27.0°±0.2° is set as I 27.0 , the strongest peak detected based on zirconium nitride at 33.9°±0.2° is set as I 33.9 In the case of , the following formula is satisfied:
[0124] 0.01≤I 35.3 / I 27.0 ≤0.5, and
[0125] 0≤I 33.9 / I 27.0 ≤1.0.
[0126] (Feature 2)
[0127] The silicon nitride sintered body according to feature 1, wherein in the XRD analysis (2θ), the strongest peak detected based on zirconium oxide at 30.1°±0.2° is set as I 30.1 In the case of , the following formula is satisfied:
[0128] 0.02≤I 30.1 / I 27.0 ≤0.30.
[0129] (Feature 3)
[0130] The silicon nitride sintered body according to feature 2, wherein in the XRD analysis (2θ), the strongest peak detected based on zirconium oxide at 28.2°±0.2° is set as I 28.2 In the case of , the following formula is satisfied:
[0131] 0.01≤I 28.2 / I 27.0 ≤0.30.
[0132] (Feature 4)
[0133] The silicon nitride sintered body according to any one of features 1 to 3, wherein in the XRD analysis (2θ), the strongest peak detected at 36.7°±0.2° is set as I 36.7 , the strongest peak detected at 41.9°±0.2° is set as I 41.9 In the case of , the following formula is satisfied:
[0134] 0≤I 36.7 / I 27.0 ≤0.50, or
[0135] 0≤I 41.9 / I 27.0 ≤0.50.
[0136] (Feature 5)
[0137] The silicon nitride sintered body according to any one of features 1 to 4,
[0138] containing the zirconium oxide particles,
[0139] The average particle size of the oxide particles is 0.05 μm or more and 2 μm or less,
[0140] In a measurement region of 100 μm×100 μm in an arbitrary cross section, the total area of the oxide particles is within a range of 0.01% to 15%.
[0141] (Feature 6)
[0142] The silicon nitride sintered body according to any one of Features 1 to 5, wherein the maximum diameter of the voids in a measurement area of 100 μm×100 μm in an arbitrary cross section is 3 μm or less.
[0143] (Feature 7)
[0144] A wear-resistant component using the silicon nitride sintered body according to any one of features 1 to 6.
[0145] (Feature 8)
[0146] A semiconductor device substrate using the silicon nitride sintered body according to any one of features 1 to 6.
[0147] (Feature 9)
[0148] A method for producing a silicon nitride sintered body, comprising the following steps:
[0149] A step of preparing a molded body by mixing silicon nitride powder and at least zirconium compound powder and molding the mixture;
[0150] A step of producing a degreased body by degreasing the formed body;
[0151] The step of placing the degreased body in a firing chamber;
[0152] The step of disposing a filling powder in the firing chamber; and
[0153] A firing step of firing the degreased body at a temperature lower than 1650° C. in the firing chamber in which the filler powder is arranged.
[0154] (Feature 10)
[0155] The method for producing a silicon nitride sintered body according to feature 9, wherein the sintering temperature in the sintering step is lower than 1550°C.
[0156] (Feature 11)
[0157] According to the method for manufacturing a silicon nitride sintered body described in feature 0, the pressure change in the sintering step is less than 0.1 MPa.
[0158] (Feature 12)
[0159] The method for producing a silicon nitride sintered body according to features 9 to 11, wherein the filler powder is one or more selected from the group consisting of silicon nitride, silicon oxide, magnesium oxide, and talc.
[0160] Several embodiments of the present invention are illustrated above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. These embodiments and their modifications are included in the scope and main purpose of the invention, and are also included in the invention recorded in the claims and their equivalents. In addition, the above-mentioned embodiments can also be implemented by combining with each other.
[0161] Explanation of symbols
[0162] 1-Bearing ball
[0163] 2-Substrates for semiconductor devices
[0164] 3- Firing room
[0165] 4-Outer wall
[0166] 5 - Inner wall
[0167] 6- Filling powder
[0168] 7-Degreased body
[0169] 8 - cover
[0170] 9 - Table surface
Claims
1. A silicon nitride sintered body comprising 0.1 mass % or more and 10 mass % or less of zirconium in terms of oxide, wherein: When performing XRD analysis (2θ) on an arbitrary cross section, the strongest peak intensity detected at 35.3°±0.2° based on the α-type silicon nitride grains is set as I 35.3 The strongest peak detected based on β-type silicon nitride grains at 27.0°±0.2° is set as I 27.0 , the strongest peak detected based on zirconium nitride at 33.9°±0.2° is set as I 33.9 In the case of , the following formula is satisfied: 0.01 ≤ I 35.3 / I 27.0 ≤0.5, and 0≤I 33.9 / I 27.0 ≤1.0。 2. The silicon nitride sintered body according to claim 1, wherein In the XRD analysis (2θ), the strongest peak detected at 30.1°±0.2° based on zirconium oxide is set as I 30.1 In the case of , the following formula is satisfied: 0.02≤I 30.1 / I 27.0 ≤0.30。 3. The silicon nitride sintered body according to claim 2, wherein: In the XRD analysis (2θ), the strongest peak detected at 28.2°±0.2° based on zirconium oxide is set as I 28.2 In the case of , the following formula is satisfied: 0.01≤I 28.2 / I 27.0 ≤0.30。 4. The silicon nitride sintered body according to any one of claims 1 to 3, wherein In the XRD analysis (2θ), the strongest peak detected at 36.7°±0.2° was set as I 36.7 , the strongest peak detected at 41.9°±0.2° is set as I 41.9 In the case of , the following formula is satisfied: 0≤I 36.7 / I 27.0 ≤0.50, or 0≤I 41.9 / I 27.0 ≤0.50。 5. The silicon nitride sintered body according to any one of claims 1 to 3, wherein containing the zirconium oxide particles, The average particle size of the oxide particles is 0.05 μm or more and 2 μm or less, In a measurement region of 100 μm×100 μm in an arbitrary cross section, the total area of the oxide particles is within a range of 0.01% to 15%.
6. The silicon nitride sintered body according to claim 4, wherein containing the zirconium oxide particles, The average particle size of the oxide particles is 0.05 μm or more and 2 μm or less, In a measurement region of 100 μm×100 μm in an arbitrary cross section, the total area of the oxide particles is within a range of 0.01% to 15%.
7. The silicon nitride sintered body according to any one of claims 1 to 3, wherein In a measurement area of 100 μm×100 μm in an arbitrary cross section, the maximum diameter of the voids is 3 μm or less.
8. The silicon nitride sintered body according to claim 5, wherein In the measurement area of 100 μm×100 μm, the maximum diameter of the voids is 3 μm or less. 9 . A wear-resistant component using the silicon nitride sintered body according to claim 1 . 10 . A wear-resistant component using the silicon nitride sintered body according to claim 7 .
11. A wear-resistant component using the silicon nitride sintered body according to claim 8. 12 . A semiconductor device substrate using the silicon nitride sintered body according to claim 1 . 13 . A semiconductor device substrate using the silicon nitride sintered body according to claim 7 . 14 . A semiconductor device substrate using the silicon nitride sintered body according to claim 8 .
15. A method for producing a silicon nitride sintered body, comprising the following steps: A step of preparing a molded body by mixing silicon nitride powder and at least zirconium compound powder and molding the mixture; A step of producing a degreased body by degreasing the formed body; The step of placing the degreased body in a firing chamber; The step of disposing a filling powder in the firing chamber; and A firing step of firing the degreased body at a temperature lower than 1650° C. in the firing chamber in which the filler powder is arranged.
16. The method for producing a silicon nitride sintered body according to claim 15, wherein: The firing temperature in the firing step is lower than 1550°C.
17. The method for producing a silicon nitride sintered body according to claim 15 or 16, wherein: The pressure change in the sintering step is 0.1 MPa or less.
18. The method for producing a silicon nitride sintered body according to claim 15 or 16, wherein: The filler powder is one or more selected from silicon nitride, silicon oxide, magnesium oxide, and talc.
19. The method for producing a silicon nitride sintered body according to claim 17, wherein: The filler powder is one or more selected from silicon nitride, silicon oxide, magnesium oxide, and talc.
Citation Information
Patent Citations
Silicon nitride sintered compact and its manufacturing method
JP2003040676A
Method for manufacturing silicon nitride ceramic sintered bodies and firing vessel
JP5811391B2
Silicon nitride powder and method for producing silicon nitride sintered body
WO2018110564A1